Antecedents and Consequences of Islamic Pawnshops: Literature Study - Shaddiq, Syahrial; Silvia, Siska; Dalem, Aria Santri; Awaludin, Ade Wahyu; Indrawan, Iin (PPSDP International Journal of Education, 2025)
Sharia pawnshops have become one of the Islamic financial instruments that contribute significantly to providing financing solutions in accordance with sharia principles. The antecedents of the success of sharia pawnshops include the level of Islamic financial literacy, public trust in sharia services, and sharia-based product innovations that are relevant to customer needs. This study aims to analyze the antecedents and consequences of sharia pawnshops through literature studies. This study was conducted through literature analysis from various academic and practical sources to identify the main factors that influence the success of sharia pawnshops and the positive impacts they generate. The results of the analysis show that the main antecedents of the success of sharia pawnshops include the level of Islamic financial literacy, public trust, and sharia-based product innovations. This study can be concluded that sharia pawnshops have a strategic role in supporting financial inclusion and sharia-based economic empowerment.